EFFECT OF DRAINAGE LAYER EFFECTIVENESS ON STRUCTURAL PERFORMANCE OF FLEXIBLE PAVEMENT SYSTEM - Vidyaning Viarsami, Vita
Moisture content is the main cause of pavement design failures both functionally and structurally. This is related to the time duration of the water flows out of the pavement system. Water trapped in the pavement system causes moisture damage, decrease in layer modulus and loss of strength, and to increase the service life of the pavement, a drainage layer which is a component of the subsurface drainage in the pavement system is needed to install so that water can discharge quickly out of the pavement. This study focuses on looking at the effect of the drainable pavement model using the ATPB (Asphalt Treated Permeable Base) as drainage layer to improve the structural performance of the flexible pavement and compared with the undrainable pavement model (without a drainage layer). The objectives of this study are to evaluate the effect of the drainage layer design property parameters on the flexible pavement system to the time – to – drain parameter, determine the time – to – drain value which is obtained from the DRIP (Drainage Requirement in Pavement) program analysis, and predict the structural performance of the drainable pavement simulation and compared with the undrainable pavement system. Based on the result of the sensitivity analysis of the design property parameters to the time-to-drain, it is known that the most sensitive parameter to the time-to-drain is the permeability. The results of the time – to – drain that were obtained from the DRIP program on the drainable pavement simulation model shows that the Asphalt Treated Permeable Base (ATPB) as drainage layer with a thickness of 15 cm and an asphalt binder of 2.5% - 3% based on laboratory experiment present fastest time – to – drain and excellent drainage quality. Meanwhile, if the drainage layer is thickened to 30cm, the time-to-drain value and the drainage quality will will be increased. The time – to – drain value of the undrainable pavement simulation model with base layer using class A aggregate material is still not faster than the drainable pavement model using ATPB as drainage layer, the result shows the time – to – drain value is 13.72 hours with good drainage quality. Based on the structural response analysis, it was found that the drainable pavement model with ATPB drainage layer is more able to withstand permanent deformation than the undrainable pavement model (without the drainage layer), so that increases the service life of flexible pavement. The thicker permeable base and pavement structure shown the better structural performance of the flexible pavement. The use of Class B Aggregate for subbase layer did not significantly increase the structural performance of the flexible pavement but could significantly reduce the maximum vertical compressive strain, especially in models with ATPB drainage layers. Based on the scenario of the groundwater table simulation (from high to low) for all soil types variation (A-4, A-6, A-7-5 and A-7-6), the higher groundwater level resulting the higher value of maximum deflection, horizontal strain and vertical compressive strain respectively. Moreover, the structural response values in the model without drainage layer showed greater value than the model with ATPB drainage layer because the modulus of ATPB drainage layer when saturated is still higher than the Class A modulus as the base layer. The drainable pavement with a thick ATPB drainage layer is the best model with the best structural performance and can accommodate all of the groundwater level scenario. As a result, this model can accommodate low to high traffic loads, FFF1 (< 2 million CESA5) to FFF6 (> 30-50 million CESA5) based on fatigue cracking performance. Furthermore, this model has the fastest time-to-drain among other models and resulting very good drainage quality, consequently influence the structural number (SN) and has the highest value among the other models.